Tingkat Pengetahuan Masyarakat Terhadap Ketepatan Swamedikasi Obat Anti Jamur di Apotek - Indrasari, Ferika; Dewi, Novita Indah Permata; Wulandari, Agustina Ratna; Solichah, Ayu Ina (Jurnal Farmasi & Sains Indonesia, 2023)
Antifungal is a class of drugs that are fungicidal or fungistatic, these drugs can be used to treat and prevent mycoses such as water fleas, ringworm. People around Wahyu Farma Pharmacy often experience itching caused by fungi or allergies. One treatment that is often done by the community is self-medication (self-medication). In self-medication, the community needs good knowledge so that self-medication can have a positive impact. The purpose of this study was to determine the level of public knowledge about the accuracy of self-medication of antifungal drugs at the Wahyu Farma Pharmacy in the Jepon area of ​​Blora City. This type of research is a non-experimental descriptive with a quantitative approach. This study uses purposive sampling method with a questionnaire measuring instrument to 95 respondents. The data obtained is primary data from the results of filling out questionnaires distributed to the community who are self-medication of antifungal drugs. The results of the study showed that the level of knowledge about self-medication was 79.47% classified as sufficient, the right category of drugs 71.57% was sufficient, the right dose was 73.15% sufficient category, on time 67.36% sufficient category, alert for side effects 62, 10% is sufficient. The total percentage of self-medication, right drug, right dose, right drug, on time, alert for side effects is 70.73% which means that they are knowledgeable enough.